2022
DOI: 10.3390/su14042384
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Growth in the Number of Patents Granted and Its Effect over the Level of Growth of the Countries: An Econometric Estimation of the Mixed Model Approach

Abstract: The purpose of this paper is to identify and measure the impact of the variables affecting the increase in the number of patents as a way to advance the development of policies in countries in terms of sustainable development based on innovation. An econometric estimation of a mixed model was used to measure the impact of patent development on the countries analyzed in this research. The findings suggest that economies that have some relevance in research and development have increasing numbers of patents. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…A patent is a legal title that protects an invention. Patent documents are a source of technological information and an indicator of R&D performance, and they can also be harnessed to guide policymaking decisions [71][72][73].…”
Section: Industrial Property As a Source Of Technological Informationmentioning
confidence: 99%
“…A patent is a legal title that protects an invention. Patent documents are a source of technological information and an indicator of R&D performance, and they can also be harnessed to guide policymaking decisions [71][72][73].…”
Section: Industrial Property As a Source Of Technological Informationmentioning
confidence: 99%
“…Bearing in mind that developed countries are characterized by a significant fund of technological knowledge and human capital (Alnuaimi et al, 2012), as well as appropriate institutional frameworks related to the protection of patents, that is, intellectual property rights (Candelin-Palmqvist et al, 2012), it can be concluded that developed countries may have better abilities to maximize utility from patents. Based on the analysis of data from 99 countries in the period 1996-2018, Rubilar-Torrealba et al (2022 claim that the more developed a country is, the more patents it tends to have. The increase in the number of patents can contribute to the development of innovations that can have a positive impact on economic growth (Marjanović et al, 2019;Caseiro & Simões, 2019;Pradhan et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patent documents, although not necessarily corresponding to innovations introduced on the market, play an important role in the innovation process, allowing the identification of technological domains that could be covered by new inventions and the relevant technologies, searches for potential partners for the development of new technologies and innovations, and the movements of other scientific, technological and market actors [15][16][17]. The relevance of technological information from the analysis of patents intensifies as an annual growth in patent documents in the world has been observed; these patents cover all technological fields and can be accessed in national or international offices with electronic media, whose systematization presents objective criteria to perform searches and collect data [18]. In 2020 alone, 3.3 million patents were filed worldwide.…”
Section: Introductionmentioning
confidence: 99%